Novel cis compound heterozygous variants in MYO6 causes early onset of non-syndromic hearing loss in a Chinese family - Ji, Haiting; Zhang, Lichun; Hussain, Hafiz Muhammad Jafar; Aftab, Ayesha; Yu, Huiqian; Xiao, Min (Frontiers in Genetics, 2024)
Mutations in the MYO6 gene have been associated with both autosomal dominant non-syndromic hearing loss (ADNSHL) and autosomal recessive non-syndromic hearing loss (ARNSHL), with a cumulative identification of 125 pathogenic variants. To investigate the underlying genetic factor within a Chinese family affected with heriditary hearing loss, prompted the utilization of highthroughput sequencing.A detailed clinical investigation was performed. Genetic testing was performed by using target panel sequencing, and Sanger sequencing. Targeted sequencing identified the variants and Sanger sequencing was employed to validate segregation of the identified variants within family.Additionally, bioinformatics analysis was performed to strenghthen our findings.Clinical investigation revealed the family members were affected by progressive and sensorineural hearing loss with an onset around 8-10 years old. Furthermore, genetic testing identified novel MYO6 variants, c.[2377T>G; 2382G>T] p.[Trp793Gly; Lys794Asn], positioned in a cis pattern, as plausible pathogenic contributors to early-onset hearing loss characterized by a severe and progressive course. Moreover, bioinformatics analysis showd disruptin in hydrogen bonding of mutant amino acids with interactive amino acids.Our research uncovered a relationship between mutations in the MYO6 gene and non-syndromic hearing loss. We identified two variants, c.[2377T>G; 2382G>T] p.[Trp793Gly; Lys794Asn] in MYO6 as strong candidates responsible for the observed progressive hereditary hearing loss. This study not only adds to our knowledge about hearing problems related to MYO6 but also reveals the presence of monogenic compound heterozygosity. Our study will provide a new sight for genetic diagnosis in such patients and their management for future use.